(untitled) (Semiárida, 2018)
There is a growing need to increase agricultural water use efficiency (EUA). Furthermore, when the product market value started to be considered, it was developed the concept of economic water productivity (PEA), defined as the value obtained per unit of water used (Us/mm). This goal can be achieved through higher EUA or by producing crops with higher unit value. At EEA INTA Anguil, La Pampa, field experiments with several winter crops (wheat with different quality, barley, safflower, and canola) were carried out in order to identify those that have highest EUA and PEA. The results of the 2011 growing season indicated that barley had the highest EUA (14,4 kg/mm) and PEA (2,6 Us/mm). Wheat showed EUA between 10,9 and 13,6 kg/mm, with highest values for group 3 quality crops, while no differences were found for PEA among qualities (1,5 to 1,8 Us/mm). Oilseeds showed a good performance with EUA of 4,8 kg/mm in canola and 5,6 kg/mm for the sunfflowers, and PEA of both oilseeds was around 2 Us/mm. Although these results are preliminary, winter-spring oilseeds appear as interesting alternatives to include in rotations.